In vitro evaluation of intra pulp chamber heating and degree of conversion of a cementation system added with TiO2 nanotubes - Ferreira, Ligia Maria Lima Andreatta (2019)
The achievement of aesthetic and long lasting ceramic adhesive restorations in teeth has always been a major objective of studies in the context of materials and techniques development. The use of resin cements could provide better outcomes, however, studies have shown that factors such as: restoration thickness color, dental structure thickness, curing light, polymerization time and energy density could influence the amount of light that reaches the resin cement layer, which may interfere in the heating of the intra pulp chamber, and in the polymerization reaction. So it is important to assess these properties, responsible for their biological results and clinical behavior. The purpose of the present study was to evaluate the temperature variations inside the pulp chamber, color stability and degree of conversion of resin cement through different curing protocols. For intra pulp chamber temperature measures, Teflon molds were milled with different depths to settle disks of bovine dentin and ceramic disks (0.5, 1.0 and 1.5 mm both), standardize of the cementation line in 100 micrometers, positioning the tip of the light curing unit (LCU) and the tip thermocouple sensor. Study design determined groups according to thickness of bovine dentin (B 0.5; B 1.0 and B1.5 mm), ceramic disk (C 0.5, C 1.0 and C 1.5 mm), and to additivation of 0.3wt% dioxide titanium nanotubes - ntTiO2 (NT) to the Relyx Ultimate (3M ESPE) (U). The temperature in the pulp chamber was measured every 10 s during 40 s of light activation with Valo (Ultradent) pre-programmed with 1000mW/cm2 irradiance. All data was evaluated regarding their homogeneity using Shapiro-Wilk test. A Variance Analysis (ANOVA) with repeated measures was conduced, followed by Sidak test (p 5%). For intra pulp chamber measures (oC), higher temperature means were observed in the group NT light cured through C 0.5+ B 0.5 mm (5.66±0.16). Lower temperature means were shown in the group U light cured through 1.5mm C 0.5 + B 0.5 mm (0.88±0.18). All groups showed intra pulp chamber temperature increasing during light activation with significant differences. Regardless materials thickness, the resin cement reinforced with ntTiO2 provided higher heating means than the group commercially available. For color stability (E), groups were determined according to the ntTiO2 additive in the resin cement (U and NT), kind of curing process (40 s of light activation or 6 min of chemical curing), ceramic thickness (C 0.5, C 1.0 and C 1.5 mm), and time of storage (24h and 8 days) (n=10). Data were obtained by Vita Easyshade (VITA) after the curing process, 24h and 8 days after dry dark storage and were submitted to a 3-way ANOVA, followed by Tukeys (p 5%). NT groups light cured through C 0.5 mm storage for 8 days, presented lower E mean values (1.47±0.88) when compared to your respective group U light cured through C 0.5mm storage for 8 days (3.07±1.07). Higher E mean values were observed in the group U chemically cured, after 24 hours of storage (11.11+2.4), followed by group U light cured though C 1.5mm (6.24+1.89). For degree of conversion, a Differential Scanning Calorimetriy (DSC) was conduced to obtain the enthalpy graphs. The enthalpies were evaluated according to the ntTiO2 additive in the resin cement (U and NT), kind of curing process (40 s of light activation or 6 min of chemical curing) and ceramic thickness (C 0.5, C 1.0 and C 1.5 mm) in triplicate method. Enthalpies (J/mg) were collected during the curing process. Data were submitted to a 2-way ANOVA for DSC, followed by Tukeys (p 5%). Higher enthalpies mean values were observed in the group U light cured trough C 0.5 mm (123.67+13) followed U light cured though C 1.0 mm (119.17+6.0). For NT groups, those light cured trough C 0.5 mm (89.76+10.1) remained close to the group U light cured trough C 1.5 mm (82.23+15.2). In conclusion, the LCU irradiation time, ceramic/dentin thickness and ntTiO2 interfered in the temperature variation inside the pulp chamber. Besides that, 0.3wt% ntTiO2 additive into resin cement increased color stability, and interfered negatively in enthalpy values related to degree of conversion.